2016
DOI: 10.1111/jnc.13843
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological evidence of specific acetylcholine transport in rat cerebral cortex and other brain regions

Abstract: Functional acetylcholine receptors (AChRs) were recently demonstrated to exist not only in the plasma membrane but also intracellularly in brain tissues. In order to activate intracellular AChRs, endogenous hydrophilic ACh must cross the plasma membrane. Here, we examined the pharmacological characteristics of this process, including whether it is mediated by active ACh uptake. When ACh esterase (AChE) was suppressed by diisopropylfluorophosphate, [ H]ACh was effectively taken up into segments of rat cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 40 publications
2
46
0
Order By: Relevance
“…In fact, the concentrations of HC‐3 and TEA used were high enough such that both drugs could act on presynaptic mAChRs (Muramatsu et al . ). Figure (a and b) show the representative results of the experiments with HC‐3 and TEA, in which not only AChE but also presynaptic mAChRs were suppressed by DFP‐pretreatment and persistent perfusion of atropine, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…In fact, the concentrations of HC‐3 and TEA used were high enough such that both drugs could act on presynaptic mAChRs (Muramatsu et al . ). Figure (a and b) show the representative results of the experiments with HC‐3 and TEA, in which not only AChE but also presynaptic mAChRs were suppressed by DFP‐pretreatment and persistent perfusion of atropine, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…; Kuhar and Simon ; Muramatsu et al . ). In subsequent superfusion experiments, however, we showed that the accumulated [ 3 H]ACh was not liberated in response to electrical stimulation (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations